Effects of Meaningful Choices in Serious Games for Meaningful Learning - Yan Wong; Theo Bothma; Annique Smith (Serious Games Society, 2024)
This action research study examines how meaningful choice design affects the overall meaningful learning experience of a virtual reality educational serious game. An intervention was developed to teach hazard detection in mines and was tested by mining engineering postgraduate students at the local tertiary institution. The study's findings revealed that meaningful choice design significantly improved the overall learning experience. This design approach empowered players to tailor their experiences based on their strengths and weaknesses, enabling them to establish a personalized flow and pace to master the content. Moreover, participants expressed that the inclusion of meaningful choice design enriched their serious game experience and, consequently, enhanced their learning outcomes. Future research on serious games should focus on exploring replayability, quantifying the impact of positive game experiences on learning, and implementing various game design principles in educational serious games. This study advances game-based education by emphasizing the benefits of using game design techniques and positive play experiences for learning.